2007
DOI: 10.1097/meg.0b013e3281532b89
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with nonvariceal upper gastrointestinal hemorrhage before and after the adoption of the Rockall score, in the Italian Gastroenterology Units

Abstract: The Rockall score enables the clinician to formulate a more precise diagnosis and substantially shortens the time in hospital, especially for patients at low-risk of rebleeding and death, so more resources can be dedicated to critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
12
1
2
Order By: Relevance
“…The male to female ratios of PU vary, but are in most studies higher than one [23,24]. Our estimated risk of PU associated with H. pylori found by us is lower than reported by others [14,25], which may reflect our study having been carried out in a community-based setting.…”
Section: Peptic Ulcercontrasting
confidence: 67%
“…The male to female ratios of PU vary, but are in most studies higher than one [23,24]. Our estimated risk of PU associated with H. pylori found by us is lower than reported by others [14,25], which may reflect our study having been carried out in a community-based setting.…”
Section: Peptic Ulcercontrasting
confidence: 67%
“…The remaining 38 articles were reviewed in full for eligibility against prespecified criteria. An additional 20 studies were excluded, leaving 18 (11,12,14,(16)(17)(18)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) in the final review. Reasons for exclusion are described in Figure 1.…”
Section: Results and Discussion Search Resultsmentioning
confidence: 99%
“…51 Given that this classification system only comprises the endoscopic description, Rockall and colleagues 52 undertook a large prospective audit in 1995 to integrate clinical parameters with endoscopic score to predict disease outcomes, including rebleeding and mortality. [53][54][55] Nevertheless, with changing epidemiology and the advent of endoscopic techniques, larger cohorts have been conducted to evaluate the risk factors. A cohort study involving 1144 patients with peptic ulcer bleeding identified several clinical and endoscopic parameters as independent factors predicting rebleeding.…”
Section: Risk Factors For Rebleedingmentioning
confidence: 99%